(3eSGFd eYOhOI ef EedGA GdTjN CHj Ydi Hf SjfGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdebGdI GdChdi (B:- (3EPG MOK ai YVh ef GdCYVGA hLY hSHHg ShA eRGL adG jecf ERGdI Pdc GdhLY s
(3BNQgG (B:s
(3Ydi cGf ef bHdfG agPG BNQ RHOI GdcdGe ai GdNdGUI fNJJe GdQSGdI s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI QVGQGeHhQ (B(423(1)) s
Keywords: (3GdWHs